2014
DOI: 10.1007/s10803-014-2109-7
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Gender Differences in Autobiographical Memory in Children with an Autism Spectrum Disorder

Abstract: Autobiographical memory was assessed in 24 children (12 male, 12 female, aged between 8 & 16 years) with autism spectrum disorder (ASD) and a comparison group of 24 typically developing (TD) children matched for age, IQ, gender and receptive language. Results suggested that a deficit in specific memory retrieval in the ASD group was more characteristic of male participants.Females in both the TD and ASD groups generated more detailed and emotional memories than males. They also demonstrated superior verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 49 publications
3
43
0
9
Order By: Relevance
“…ASD patients frequently display atypical cognitive performance, such as impaired social cognition (Lai et al ., ), while object recognition is often intact (Dawson et al ., ). Interestingly, female patients demonstrate better access to emotionally salient memories than males (Goddard et al ., ). Consistent with these findings, we found that male, but not female, rats prenatally exposed to VPA showed deficits in social discrimination from infancy till adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…ASD patients frequently display atypical cognitive performance, such as impaired social cognition (Lai et al ., ), while object recognition is often intact (Dawson et al ., ). Interestingly, female patients demonstrate better access to emotionally salient memories than males (Goddard et al ., ). Consistent with these findings, we found that male, but not female, rats prenatally exposed to VPA showed deficits in social discrimination from infancy till adulthood.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, by restricting our sample to high‐functioning ASD we successfully controlled for nonspecific, IQ‐related confounding effects on sleep–dependent memory, although the findings may not be considered representative for low‐functioning ASD children. Because our experimental design was tailored to minimize variance by recruiting homogeneous groups of boys only, we cannot generalize our findings to girls with ASD who may differ in memory processing from boys with ASD (Goddard, Dritschel, & Howlin, ). Furthermore, although analyses showed that the presence of comorbidities explained only a small amount of variance, future studies with larger samples should systematically investigate a possible contribution of comorbid diagnosis to the observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of non-core-symptoms was beyond the scope of this report; however, previous research has indicated differences between males and females in several specific domains including executive functioning (e.g. Bölte et al, 2011; Lai et al, 2012; Lemon et al, 2011), perceptual attention to detail and motor function (Lai et al, 2012), adaptive skills (Frazier et al, 2014), autobiographical memory (Goddard et al, 2014) and sleep habits (Hartley et al, 2009). Such factors could interact with core-symptom presentation and may contribute to a definition of sex-specific manifestations of the ASD phenotypes.…”
Section: Discussionmentioning
confidence: 99%